Compositional Analysis of Grape Berries: Mapping the Global Metabolism of Grapes - Huanteng Hou; Yufei Li; Shen Zhou; Ran Zhang; Yuanyue Wang; Long Lei; Chenkun Yang; Sishu Huang; Hang Xu; Xianqing Liu; Min Gao; Jie Luo (Foods)
To characterize the nutrients and bioactive compounds in grape berries and to explore the real cause of the “French paradox” phenomenon, we performed metabolomic analysis of 66 grape varieties worldwide using liquid chromatography–tandem mass spectrometry (LC-MS). A nontargeted metabolomics approach detected a total of 4889 metabolite signals. From these, 964 bioactive and nutrient compounds were identified and quantified, including modified flavonoids, medicinal pentacyclic triterpenoids, vitamins, amino acids, lipids, etc. Interestingly, metabolic variations between varieties are not explained by geography or subspecies but can be significantly distinguished by grapes’ color, even after excluding flavonoids and anthocyanins. In our analysis, we found that purple grape varieties had the highest levels of key bioactive components such as flavonoids, pentacyclic triterpenes, and polyphenols, which are thought to have a variety of health benefits such as antioxidant, anti-inflammatory, and antitumor properties, when compared to grapes of other colors. In addition, we found higher levels of vitamins in red and pink grapes, possibly explaining their role in preventing anemia and scurvy and protecting the skin. These findings may be a major factor in the greater health benefits of wines made from purple grapes. Our study provides comprehensive metabolic profiling data of grape berries that may contribute to future research on the French paradox.